Regulating panicle nitrogen fertilizers for qualities of rice with different grain filling rate in China - Ding, Chao; Luo, Xikun; Wang, Zichen; Wu, Longmei; Zhang, Jianwei; Xu, Liping; Jin, Ting; Guan, Yongxiang; Long, Weihua (Frontiers in Agronomy, 2026)
IntroductionPanicle nitrogen fertilizer is an important agronomic measure to regulate rice quality. Grain filling is crucial for the formation of rice quality. However, there are few studies on the effects of panicle nitrogen application on rice quality of soft japonica rice with different grain filling rate.MethodsIn this study, two field experiments were carried out, two soft japonica rice varieties, Ningxiangjing 9 (N9) with rapid grain-filling rate and Ningjing 8 (N8) with slow grain-filling rate, were used under four panicle nitrogen levels.Results and discussionN9 exhibited significant increase in chalkiness rate and chalkiness degree under medium to high panicle nitrogen levels, while panicle nitrogen fertilizer application had relatively smaller effects on N8. With the increasing panicle nitrogen level, N9 demonstrated greater improvement in processing quality compared to N8 under environmental with lower soil fertility, Conversely, N9 showed smaller reduction in processing quality compared to N8 under environmental with higher soil fertility. With increasing nitrogen application rates in panicle fertilizers, N8 showed greater decreases in taste quality under medium to high nitrogen levels compared to N9. In conclusion, the key to achieving high-quality rice production in the field lies in formulating differentiated panicle nitrogen fertilizer management strategies based on the grain filling rate characteristics of the varieties.